Decreased IgG Antibody Response to Viral Protein Mimotopes of Oncogenic Merkel Cell Polyomavirus in Sera From Healthy Elderly Subjects - Mazziotta, Chiara; Lanzillotti, Carmen; Govoni, Marcello; Pellielo, Giulia; Mazzoni, Elisa; Tognon, Mauro; Martini, Fernanda; Rotondo, John Charles (Frontiers in Immunology, 2021)
Merkel cell polyomavirus (MCPyV) is the main causative agent of Merkel cell carcinoma (MCC), a rare but aggressive skin tumor with a typical presentation age >60 years. MCPyV is ubiquitous in humans. After an early-age primary infection, MCPyV establishes a clinically asymptomatic lifelong infection. In immunocompromised patients/individuals, including elders, MCC can arise following an increase in MCPyV replication events. Elders are prone to develop immunesenescence and therefore represent an important group to investigate. In addition, detailed information on MCPyV serology in elders has been debated. These findings cumulatively indicate the need for new research verifying the impact of MCPyV infection in elderly subjects (ES). Herein, sera from 226 ES, aged 66–100 years, were analyzed for anti-MCPyV IgGs with an indirect ELISA using peptides mimicking epitopes from the MCPyV capsid proteins VP1-2. Immunological data from sera belonging to a cohort of healthy subjects (HS) (n = 548) aged 18–65 years, reported in our previous study, were also included for comparisons. Age-/gender-specific seroprevalence and serological profiles were investigated. MCPyV seroprevalence in ES was 63.7% (144/226). Age-specific MCPyV seroprevalence resulted as 62.5% (25/40), 71.7% (33/46), 64.9% (37/57), 63.8% (30/47), and 52.8% (19/36) in ES aged 66–70, 71–75, 76–80, 81–85, and 86–100 years, respectively (p > 0.05). MCPyV seroprevalence was 67% (71/106) and 61% (73/120) in ES males and females, respectively (p > 0.05). Lack of age-/gender-related variations in terms of MCPyV serological profiles was found in ES (p > 0.05). Notably, serological profile analyses indicated lower optical densities (ODs) in ES compared with HS (p < 0.05), while lower ODs were also determined in ES males compared with HS males (p < 0.05). Our data cumulatively suggest that oncogenic MCPyV circulates in elders asymptomatically at a relatively high prevalence, while immunesenescence might be responsible for a decreased IgG antibody response to MCPyV, thereby potentially leading to an increase in MCPyV replication levels. In the worse scenario, alongside other factors, MCPyV might drive MCC carcinogenesis, as described in elders with over 60 years of age.